Scholarship on Women and Policing: Trends and Policy Implications. (October 2014) - Kringen, Anne Li
A systematic review of the literature on women and policing for the period of 1972 to 2012 was undertaken to determine how gender was incorporated in research and how this scholarship changed over time. The analysis indicates that the majority of research on women in policing is typically directed at understanding the role of gender in policing. The volume of published research increased over the period, but of the three major domains of research (job performance, job experience, and blocked opportunities), the majority of growth occurred in job experience domain. Blocked job opportunity research, which has important policy implications, experienced only a moderate increase. The majority of research on women in policing was found to be published in specialty academic journals including gender specialty journals and policing specialty journals. The impact of publishing primarily in these outlets is discussed.